Determination of the critical parameters of the technological process of obtaining solid dosage forms with dry extract and crushed roots and rootes of Scutellaria baicalensis - G. D. Slipchenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
An important condition for obtaining a high-quality drug is the determination of critical points and parameters of the production process, which is divided into several successive stages. The aim study of the critical parameters of the production of tablets and capsules with vegetable raw materials. For this purpose, validation studies of technological processes were carried out for tablets with dry extract of Scutellaria baicalensis and hard gelatin capsules with vegetable raw materials. The subject of our research was the technological process of obtaining tablets based on dry extract of the roots and rhizomes of Baikal skullcap and hard gelatin capsules based on crushed raw materials. We have identified critical process parameters for each stage. Validation tests were carried out for certain critical process parameters and acceptance criteria were calculated. Quality control of finished tablets based on dry extract of Baikal skullcap and finished hard gelatin capsules based on crushed roots and rhizomes of Baikal skullcap was performed according to the following indicators: appearance, identification, average weight, mass uniformity, disintegration, dissolution, abrasion, microbiological purity, quantitative determination . The obtained validation data of experimental-industrial series meet the acceptance criteria, and the developed technology is reproducible and promising for further validation. On the basis of the obtained results, it can be concluded that the established critical values of the parameters of the production processes and their conditions of carrying out allow for stable and reliable production of semi-finished and finished products that meet the quality standards in accordance with regulatory documents.